“Somebody do Something!”: Lynching Photographs, Historical Memory, and the Possibility of Sympathetic Spectatorship - Amy Louise Wood (European Journal of American Studies)
This paper traces the history of one specific photograph and its exhibition over time from the 1930s through the 1980s: that of the lynching of ‘Bootjack’ McDaniels, tortured to death by a white mob in Duck Hill, Mississippi, in 1937. I use that history to reflect more broadly on how lynching photographs have shaped popular consciousness about racist violence at different moments in time. They are able to do so, in good part, because of their iconographic qualities. These photographs, like many historical photographs, tend to detach past events from historical specificity and, subsequently, render the past into symbolic form, which allows new meanings to be imposed on them through the text and context that surround them. Those new meanings can direct viewers’ emotional responses to the images. This process of recontextualization allows for a meaningful ethical engagement with both historical and present-day suffering. In these ways, lynching photographs have been crucial to the formation of black historical memories of violence and injustice in the United States. Through this same process of recontextualization, I argue, lynching photographs make it possible for white Americans to engage ethically with racist violence, in the past and the present, through what I call “sympathetic spectatorship,” – an emotionally empathic form of looking that also involves an awareness of social difference.